Questions concerning the law of nature - Locke, John, 1632-1704 (Book collections on Project MUSE., 1990)
John Locke's untitled manuscript "Questions Concerning the Law of Nature" (1664) was his only work focused on the subject of natural law, a circumstance that is especially surprising since his published writings touch on the subject frequently, if inconclusively. Containing a substantial apparatus criticus, this new edition of Locke's manuscript is faithful to Locke's original intentions.